The Descriptive Epidemiology of Yersiniosis: A Multistate Study, 2005–2011. (May 2015) - Chakraborty, Apurba; Komatsu, Kenneth; Roberts, Matthew; Collins, Jim; Beggs, Jennifer; Turabelidze, George; Safranek, Tom; Maillard, Jean-Marie; Bell, Linda J.; Young, David; Marsden-Haug, Nicola; Klos, Rachel F.; et al.
Objectives: Yersiniosis, a foodborne infection of zoonotic origin caused by the bacteria Yersinia enterocolitica and Yersinia pseudotuberculosis, is a reportable disease in 38 states. Both sporadic and foodborne outbreaks of yersiniosis have been reported in the U.S., with annual occurrence of an estimated 98, 000 episodes of illness, 533 hospitalizations, and 29 deaths. We analyzed surveillance data from nine non-FoodNet-participating U.S. states during the period 2005–2011 to describe the epidemiology of this disease. Methods: As part of a passive surveillance system, laboratory-confirmed cases of yersiniosis were reported to state health departments in Arizona, Illinois, Michigan, Missouri, Nebraska, North Carolina, South Carolina, Washington, and Wisconsin. We calculated overall, age-, and race-specific annual incidence rates per 100, 000 population using 2010 Census data as the denominator. We used Poisson regression to examine seasonal variation and annual incidence trends by race, age group, and overall. Results: The average annual incidence of yersiniosis was 0.16 cases per 100, 000 population during 2005–2011. We observed a statistically significant decreasing annual trend of yersiniosis incidence among African Americans <5 years of age ( p <0.01), whereas white people aged 19–64 years ( p =0.08) and Hispanic people ( p =0.05) had an overall increasing annual incidence of yersiniosis. We observed higher incidence during October–December ( p <0.01) and January–March ( p =0.03) quarters among African Americans, whereas white people had a higher incidence during April–June ( p =0.05). Conclusion: This multistate analysis revealed differences in the epidemiology of yersiniosis by race/ethnicity that may be useful for future research and prevention efforts. While this study was consistent with the FoodNet report in recognizing the high and declining incidence among African American children and winter seasonality among African Americans, our study also identified April–June seasonality among the white population.